Optimizing effort for profit and sustainability: a bioeconomic and environmental evaluation of the Namibian hake fishery - Nalukaku, Tomas; Mueni, Laurine Mule; Adebote, Mary Opeyemi; Darko, George; Olowe, Olumide Samuel; Namboga, Anna-Marie; Muhammad, Kabiru; Gebauer, Radek; Folorunso, Ewumi Azeez (Frontiers in Marine Science, 2025)
The Namibian hake fishery plays an essential role in both the national economy and marine biodiversity conservation. However, recent reports of declining catch volumes and profitability have raised concerns over the biological and economic sustainability of fishery. This study analyzes a 24-year dataset (2000-2024) using the Gordon-Schaefer bioeconomic model to assess sustainability, with a focus on defining Maximum Sustainable Yield (MSY), Maximum Economic Yield (MEY), and associated effort thresholds for two vessel types: wet-fish (DW) and freezer vessels (DF). In addition, using multivariate regression, we assessed the influence of environmental drivers, such as sea surface and bottom temperature anomalies, gear depth, haul duration, number of hauls, and spatial distribution. Haul duration was the only significant predictor (β = –69,179; p = 0.014), while bottom and surface temperature, mean gear depth, latitude, and number of hauls were not statistically significant (p > 0.05). The bioeconomic model outcome reveals a long-term decline of catch and CPUE trends, with historical lows recorded in 2024. The model’s estimated overall MSY was 132,832 tonnes with an EMSY (Ecosystem-based Maximum Sustainable Yield) of 53,534 hours, while MEY and EMEY (Ecosystem-based Maximum Economic Yield) were 125,413 tonnes and 38,188 hours, respectively. However, with the actual effort levels exceeding these thresholds, the findings suggest potential overexploitation and reduced economic efficiency. About 44% of the variance in catch by DF trawlers were explained by the bottom temperature model (R² = 0.44, Adj. R² = 0.37, p = 0.008). However, univariate relationships should be interpreted cautiously and primarily as exploratory patterns. Spatially, higher CPUE clusters were recorded between latitudes 24°S–28°S and at depths of 300–400 m. The economic assessments from 2018 and 2023 showed negative profitability when only hake revenue was considered, with breakeven prices increasing due to operational costs. However, profitability was attainable with the inclusion of ancillary revenues such as by-catch sales and quota leasing. Our study identifies the need to align fishing efforts with MEY to improve sustainability and economic returns. Long-term resilience of the hake fishery under changing climate can be achieved through stock rebuilding, adaptation to environmental variability, and implementation of cost-effective strategies.